The encyclopedia of middle grades education - Mertens, Steven B.; Caskey, Micki M.; Flowers, Nancy (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
The second edition of The Encyclopedia of Middle Grades Education has been revised, updated, and expanded since its original publication in 2005. The Encyclopedia is a comprehensive overview of the field; it contains alphabetically organized entries that address important concepts, ideas, terms, people, organizations, publications, and research studies specifically related to middle grades education. This edition contains over 210 entries from nearly 160 expert contributors, this is a 25% increase in the number of entries over the first edition. The Encyclopedia is aimed at a general audience including undergraduate students in middle-level teacher preparation programs, graduate students, higher education faculty, and practitioners and administrators. The comprehensive list of entries are comprised of both short entries (500 words) and longer entries (2000 words). A significant number of entries appearing in the first edition have been revised and updated. Citations and references are provided for each entry.
Keywords: Middle school education -- Encyclopedias.; Education -- Administration -- Elementary & Secondary.; Primary and middle schools.; Educational administration and organization.; Secondary schools.; elektronické knihy; electronic books